Enteral vitamin A for reducing severity of bronchopulmonary dysplasia in extremely preterm infants: a randomised controlled trial - Abhijeet Rakshasbhuvankar; Sanjay Patole; Karen Simmer; J. Jane Pillow (BMC, 2017)
Abstract Background Intramuscular vitamin A supplementation decreases the risk of bronchopulmonary dysplasia (BPD) in very-low-birth-weight preterm infants without significant adverse effects. However, intramuscular vitamin A supplementation is not widely accepted because of the discomfort and risk of trauma associated with repeated injections. Enteral vitamin A supplementation has not been studied adequately in the clinical trials. Enterally administered water-soluble vitamin A is absorbed better than the fat-soluble form. We hypothesised that enteral administration of a water-soluble vitamin A preparation will decrease severity of BPD compared with a control group receiving placebo. Methods We plan a double-blind randomised placebo-controlled trial at a tertiary neonatal-perinatal intensive care unit. Eligibility criteria include infants born at less than 28 weeks' gestational age and less than 72 h of life. Infants with major congenital gastrointestinal or respiratory tract abnormalities will be excluded. After parental consent, infants will be randomized to receive either enteral water-soluble vitamin A (5000 IU once a day) or placebo. The intervention will be started within 24 h of introduction of feeds and continued until 34 weeks' post-menstrual age (PMA). The primary outcome is severity of BPD at 36 weeks' PMA. Severity of BPD will be assessed objectively from the right-shift of the peripheral oxyhaemoglobin saturation versus partial pressure of inspired oxygen (SpO2-PiO2) curve. We require 188 infants for 80% power and 5% significance level based on an expected 20% decrease in the right shift of the SpO2-PiO2 curve in the vitamin A group (primary outcome) compared with control group at 36 weeks' PMA, and a 20% attrition rate. Secondary outcomes will be plasma and salivary concentrations of vitamin A on day 28 of the trial (first 30 infants), lung and diaphragm function, clinical outcomes at 36 week' PMA or before discharge/death, and safety of vitamin A. Discussion BPD poses a significant economic burden on the health-care system. If our study shows that enteral supplementation of water-soluble vitamin A is safe and effective for decreasing the severity of BPD, it will provide the opportunity to further evaluate a simple, globally acceptable preventive therapy for BPD. Trial registration ANZCTR; ACTRN12616000408482 (30th March 2016).